Management and outcome trends in type 2 myocardial infarction: an investigation from the SWEDEHEART registry - K. M. Eggers; T. Baron; A. R. Chapman; A. Gard; B. Lindahl (Scientific Reports, 2023)
Abstract Despite poor prognosis, patients with type 2 myocardial infarction (MI) tend to be underdiagnosed and undertreated compared to those with type 1 MI. Whether this discrepancy has improved over time is uncertain. We conducted a registry-based cohort study investigating type 2 MI patients managed at Swedish coronary care units (n = 14,833) during 2010–2022. Multivariable-adjusted changes (first three vs last three calendar years of the observation period) were assessed regarding diagnostic examinations (echocardiography, coronary assessment), provision of cardioprotective medications (betablockers, renin–angiotensin–aldosterone-system inhibitors, statins) and 1-year all-cause mortality. Compared to type 1 MI patients (n = 184,329), those with type 2 MI less often had diagnostic examinations and cardioprotective medications. Increases in the use of echocardiography (OR 1.08 [95% confidence interval 1.06–1.09]) and coronary assessment (OR 1.06 [95% confidence interval 1.04–1.08]) were smaller compared to type 1 MI (pinteraction < 0.001). The provision of medications did not increase in type 2 MI. All-cause mortality rate in type 2 MI was 25.4% without temporal change (OR 1.03 [95% confidence interval 0.98–1.07]). Taken together, the provision of medications and all-cause mortality did ot improve in type 2 MI despite modest increases in diagnostic procedures. This emphasizes the need of defining optimal care pathways in these patients.